INTESTINAL PARASITES, NUTRITIONAL STATUS AND COGNITIVE FUNCTION AMONG PRIMARY SCHOOL PUPILS IN ILE-IFE, OSUN STATE, NIGERIA - Olopade, Bolatito Opeyemi; Idowu, Clement Oluwaseun; Oyelese, Adesola Olaniyan; Aboderin, Aaron Oladipo (African Journal of Infectious Diseases (AJID), 2018)
Background: Intestinal parasites are a cause of morbidity and mortality throughout the world particularly indeveloping countries and they are common health problems of children. This study determined the prevalence ofintestinal parasites among primary school children, assessed risk factors predisposing to infection and the nutritionalstatus with cognitive function of the pupils.Materials and Methods: It was a cross sectional study and 384 pupils from six public primary schools in Ile-Ife wereenrolled. Anthropometric measurements were obtained using standard procedures. The intelligence quotients of thepupils were assessed using the Draw-a-person- test. Stool samples were collected and examined. Data was processedusing SPSS Inc USA version 17. Statistical analysis was done using frequency, percentages, tables and Pearson’s chisquarewas used to determine the association between intestinal parasites, nutritional status and cognitive function.Results: The prevalence of intestinal parasites in the study population was 24% with double infection occurring in3.2%. Ascaris lumbricoides most prevalent 22.1%, Hookworm 3.4%, Hymenolepis nana 0.3%. Intestinal parasites werepresent in those that use bush and refuse dump for defeacation. The nutritional status of the pupils showed 95.8%normal weight, 3.6% underweight and 0.5% overweight. In terms of cognition, 65.4% mentally deficient, 14.3%mentally dull and 20.3% average.Conclusion: Intestinal parasites were prevalent among primary school children and use of bush or refuse dump fordefeacation was a risk factor. There was no association between intestinal parasites, nutritional status and cognition.